Investigating the factors influencing RDX shock sensitivity - Hudson, R J (Cranfield University, 2012)
The shock sensitivity of RDX (cyclotrimethylenetrinitramine) is dependent upon factors including crystal size, morphology, internal defects, surface defects and HMX content. With the arrival of reduced sensitivity RDX (RSRDX) and the drive towards insensitive munitions (IM), understanding what influences sensitivity has become a significant topic within energetic materials research. During the RS-RDX international Round Robin Study (R4) the parameters which influence sensitivity were investigated, however large discrepancies were seen between different laboratories so the results were inconclusive. The objective of this work is to clarify how crystal properties and the manufacturing process affect RDX sensitivity. In this study the same RDX lots as those from the R4 were examined. Optical microscopy showed that internal defect content varied widely and was affected by the manufacturing process. A good correlation between sensitivity and defect quantity was seen for RDX lots produced by the same method. Likewise, microscopic examination also showed a large range of morphologies which was influenced by method of production. Scanning electron microscopy also showed that surface defects were approximately correlated to shock sensitivity, however general surface roughness agreed better with sensitivity than the number of specific defects such as cracks and holes. The mechanical properties of the RDX samples were investigated using nanoindentation. This showed a good correlation between the quantity of internal defects and modulus of elasticity, hardness and creep. There was also a good agreement between these parameters and sensitivity. Rheological analysis of RDX/polyethylene glycol suspensions indicated a good agreement between the rheological properties of the suspension and crystal morphology. This method could form a basis for a new testing method for RDX morphology. Differential scanning calorimetry demonstrated that crystal size influenced decomposition rate. The melting endotherm onset temperature and energy was correlated with HMX quantity.